Peran Pengembangan Potensi Diri dalam Menemukan dan Mengasah Minat Bakat - Avisa Claresta Dewi; Edy Soesanto; Lutfiana Qorisya Azmy (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Interest in learning is an important factor that influences learning success. This interest is influenced by internal factors, such as motivation and learning style, as well as external factors, such as parental support, facilities, and the school environment. Low interest in learning has a negative impact on student learning outcomes. Therefore, strategies are needed to improve it, such as the use of creative learning methods, active student participation, parental attention, and a conducive school environment. In addition, the hope of developing self-potential is an important aspect in the formation of adaptive and competitive characters. Its implementation involves education, training, motivation, and environmental support. Individual awareness of their strengths and weaknesses, access to resources, and guidance also play a role in self-development. A holistic approach in this process is important to realize individual potential that is beneficial to oneself and society.